2014
DOI: 10.14210/bjast.v18n2.p19-29
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the abundance and biomass of zooplankton from shallow mudflat river-estuarine system in Persian Gulf

Abstract: The present study was designed to investigate the seasonal changes in the abundance and biomass of zooplankton and their relationships with water quality parameters in mudflat shallow estuary, Helleh River, Persian Gulf (Iran). The zooplankton consisted of Acartia sp., Euterpina sp., Oithona spp., Oncaea sp., Paracalanus sp., Corycaeus sp., Labidocera sp., Macrosetella sp., Microsetella sp., Temora sp., copepod copepodid, copepod nauplii, Barnacle, Polychaeta, Conchoecia sp. (Ostracoda), Hyperid, Decapoda (zoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
1
2
0
1
Order By: Relevance
“…They are main grazers of microzooplankton and phytoplankton and they play the role of prey for zooplanktivorous fishes and 449 invertebrates (Benfield 2013). A similar situation has been reported in other estuaries (Primo et al 2009;Hwang et al 2010;Xuelu et al 2011;Farhadian and Pouladi 2014). Also, copepods nauplii as a wide variety of species were observed in Mond River estuary, which occurred in appreciable amounts.…”
Section: Resultssupporting
confidence: 52%
“…They are main grazers of microzooplankton and phytoplankton and they play the role of prey for zooplanktivorous fishes and 449 invertebrates (Benfield 2013). A similar situation has been reported in other estuaries (Primo et al 2009;Hwang et al 2010;Xuelu et al 2011;Farhadian and Pouladi 2014). Also, copepods nauplii as a wide variety of species were observed in Mond River estuary, which occurred in appreciable amounts.…”
Section: Resultssupporting
confidence: 52%
“…Seasonal differences in plankton composition and biomass have been described from a variety of marine environments. In high latitudes like the Barents Sea this is mainly related to water mass circulation and bottom topography (Araskkevich et al 2002) and in a tropical estuarine system in the Persian Gulf the observed changes were mainly related to salinity, chlorophyll a, temperature and pH differences (Farhadian & Pouladi 2014). Other examples of changes in plankton composition and abundance along coastal settings ).…”
Section: Discussionmentioning
confidence: 99%
“…These ratios (measured in the photic zone during the sediment trap exposure) are useful to check the contribution level of the zooplankton ecosystem (via grazing) to carbon sinking. Significant correlations between zooplankton abundance and Chla concentration have been observed in estuarine waters (Lopes et al, 1998;Farhadian and Pouladi, 2014). The Valo Grande water column showed PhaeP concentrations higher than Chla and no increased percentages of POM and PhaeP from the water column to V-Trap collectors (Figure 17).…”
Section: Stationmentioning
confidence: 96%